TINJAUAN PENGGUNAAN REKENING BERSAMA DALAM PERJANJIAN JUAL BELI ONLINE MELALUI TOKOPEDIA - Irsyad Afif; Yudho Taruno Maryanto (Fakultas Hukum Universitas Sebelas Maret, 2021)
AbstractThis article aims to examine the legal issues to examine implementation of the sale and purchase agreement and the sale and purchase dispute settlement in the escrow account trading system, which has recently become a necessity for the wider community in e- commerce agreements, especially through Tokopedia whether it is in accordance with Indonesian laws or even violates the rules. The research method used is normative legal research and sources of legal materials used are primary legal materials and secondary legal materials by means of literature study through books and laws or from the results of previous scientific papers both thesis and journal. The results of this study uncover that the settlement of the sale and purchase dispute can violate the applicable law in Indonesia because it enforces that the decision made by Tokopedia as mediator is a final decision that cannot be contested where it is not in accordance with article 38 paragraph 1 of the ITE Law which contains